Influence of the means of general physical training on the development of high-speed abilities in boys and girls at the stage of initial training in athletics - Н.А. Вродзинский; Т.И. Дорофеева; В.А. Коробейник (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The purpose of the study is to investigate the difference in the development of high-speed and speed-strength qualities of girls and boys with identical training in the process of general physical training of young athletes in the application of a set of exercises for general physical training. Material and methods. The study was attended by 30 students: 15 girls and 15 boys aged 9-12 years. The group was represented by children who expressed their desire to enroll in the athletics circle in the Youth Sports School and have passed a preliminary test at an adequate level corresponding to the average indicators for this age group. The average age of students in the group of boys was 10.7 years, in the group of girls - 10.5 years. The preliminary testing of the DUSSS group was carried out according to three parameters: running 30 m as a speed indicator; Running 3 * 10 m as an indicator of swing; jump in length from place as indicator of high-speed force. The training was conducted according to the same scheme for girls and boys, and the test data were analyzed separately. Preparation for the developed methodology was conducted for 6 months. At the end of the experiment, a control test was performed on the same parameters and in the same conditions as in the beginning of the experiment. Results. It was found that the groups of boys and girls differed significantly among themselves only on the indicator "Running 3X10 m" (p <0,05). This is typical of comparing the testing of boys and girls to the experiment and comparing the testing performance between boys and girls after the experiment. According to other indicators, there were no significant differences between the groups of boys and girls either before or after the experiment (p> 0.05). The high reliability (at p <0.001) of the correlation between the test parameters for both groups at all stages of testing was revealed. Conclusion. There was a trend in the presence of differences in the response to the load between girls and boys of 10 years at the initial stage of training in athletics, but this difference is reliable only for the test "Running 3х10 m".